Simple hypertrophic tonsils have more active innate immune and inflammatory responses than hypertrophic tonsils with recurrent inflammation in children - Qun Huang; Hu Hua; Wei Li; Xi Chen; Lei Cheng (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Tonsil hypertrophy has negative impact on children’s health, but its pathogenesis remains obscure despite the fact that numerous bacteriological studies have been carried out. Understanding the innate immune and inflammatory states of hypertrophic tonsils with different clinical manifestations is of great significance for defining the pathogenesis of tonsil hypertrophy and establishing treatment strategies. The present study was undertaken to examine the characteristics of innate immunity and inflammation in children with hypertrophic palatine tonsils and different clinical manifestations. Methods Tonsil tissues were surgically removed from the patients and classified based on the patients’ clinical manifestations. The patients were divided into three groups: 1) Control group; 2) Tonsil Hypertrophy (TH) group; and 3) Tonsil Hypertrophy combined with Recurrent Infection (TH + RI) group. The immune and inflammatory statuses of these tissues were characterized using qRT-PCR and ELISA methods. Results Viral protein 1 (VP1) was highly expressed in TH group, but not in TH + RI group. In TH group, elevated expression was observed in the innate immune mediators, including retinoic acid-inducible gene I (RIG-I), interferon alpha (IFN-α), mitochondrial antiviral-signaling protein (MAVS), NLR family pyrin domain containing 3 (NLRP3), toll-like receptor (TLR) 4 and TLR7. Consistent with the innate immune profile, the expression of inflammatory markers (IL-1β, NF-κB and IL-7) was also significantly elevated in TH group. Meanwhile, the COX-2/PGE2/EP4 signaling pathway was found to be involved in the inflammatory response and the formation of fibroblasts. Conclusions Innate immune and inflammatory responses are more active in simple hypertrophic tonsils, rather than hypertrophic tonsils with recurrent inflammation. A local relative immune deficiency in the hypertrophic tonsils may be a causative factor for recurrent tonsillitis in TH + RI. These differences, together with the patient’s clinical manifestations, suggest that tonsillar hypertrophy might be regulated by diverse immune and/or inflammatory mechanism through which novel therapeutic strategies might be created.